ANALYTICAL HIERARCHY PROCESS SEBAGAI EVALUASI SUPPLIER ALAT KESEHATAN DAN OBAT – OBATAN DI RUMAH SAKIT MUHAMMADIYAH - Abdurrahman Faris Indriya Himawan (Jurnal Manajerial, 2019)
Supplier selection is one of the important things in purchasing activities for companies, because the selection of suppliers is very influential on the quality of a product. One way to choose the right supplier for the company can be done using the Analytical Hierarchy Process (AHP) method, the Analytical Hierrarchy Process method is a decision-making method developed to give priority to several alternatives when several criteria must be considered. Some things to consider in choosing suppliers such as: shipping, quality, service, past performance, payment. This research was conducted at one of Muhammadiyah's charitable businesses, namely at the Muhammadiyah Hospital or Clinic. This study aims to find out the best supplier for Muhammadiyah Hospital. This study uses a quantitative descriptive research approach. With the use of samples from this study is the decision making in the purchase of drugs and medical devices Clinic or Muhammadiyah Hospital. The results of the data analysis concluded that the indicators of quality, acceleration of service, credibility of suppliers are bets in determining the best suppliers for the procurement of drugs and medical devices clinics or hospitals Muhammadiyah. Whereas from the overall simulation results Supplier Q is considered as the best supplier for Muhammadiyah Hospital, because overall of all criteria Supplier Q has the highest value compared to other suppliers.